SWOT Strategy in Strengthening the Economy Based on “Kampung Keren” through the D’Cito Program - Titin Trimintarsih; Lana Adi Tania Tania; Nizar Zakaria (JURNAL EKUIVALENSI, 2026)
The D’Cito Program in Kediri City develops the city’s identity through clustered kampungs, known as Kampung Keren, consisting of 22 kampungs. Out of these, 6 kampungs have advanced, while 16 kampungs remain at the pioneering stage. Data from 2024 show that although the number of tourists continues to increase, the growth rate has declined. The research problem addressed in this study is how to develop the 16 pioneering Kampung Keren so that they can progress, attract more tourists, and improve the local economy. The problem is analyzed using SWOT analysis. The results indicate that the clustered kampungs in Kediri City are in a Progressive position (S-O Strategy), which means there is a need for synergy between the government and the community by focusing on human resource (HR) development and intensifying promotion to ensure the sustainability of Kampung Keren, thereby strengthening business competitiveness and the local economy.